The Effect of Immune responses In Pathogenesis of Hepatitis B Virus Patients - alwan, J abbar afat; Njum, Ali Anok (International Journal of Psychosocial Rehabilitation, 2020)
Study attempts to estimate immune molecules CD45- R & CD79 and cytokines TNF-α and IL-6 in patients infected with HBV A total of (100) seropositive patients for HBV were screened for this study .Patients attended general lab, because of abdominal pain , jaundice and loss of appetite and other liver complaint, any serum samples expressed positive for anti-HBV antibodies directly choose to show level of TNF-α & IL-6 in serum of patient and show expression of CD45-R and CD79. Results showed that serum samples were analyzed for IL-6 & TNF-α by ELISA , showed highly significant increases (p<0.05) in serum level of HBV patients as compared with healthy control groups , acute HBV revealed high as well as , increases in serum level of TNF-α significantly(p<0.05) ,while chronic liver disease patients express high increase in serum level of IL-6 significantly(p<0.05).Activated markers study revealed high expression of CD79 & CD45-R in HBV patients as compared with healthy normal groups